PERBANDINGANSISTEM EFISIENSI KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL (Studi kasus Bank Sumut Syariah KCP Stabat dan Bank Sumut KCP. Stabat) - Desi Afrida; Diyan Yusri; Anjur Perkasa Alam (EKSYA : Jurnal Ekonomi Syariah, 2023)
The purpose of this research is to find out the Financial Performance of Bank SUMUT Syariah Kcp.stab.To find out the Financial Performance of conventional Banks.To find out the difference between the financial performance of Islamic banks and conventional banks.Field research was used to obtain the data needed in this study, namely by using data collection tools through observation, interviews or structured interviews, and documentation.The data obtained was then processed and analyzed.In this study, qualitative research was used with an analytical description approach, namely by describing the research results obtained through structured interviews on research sources. The results of financial performance research are the results of operational activities which are presented in the form of financial figures. The results of the company's activities for the current period must be compared with financial performance in the past, budget, balance sheet and average profit and loss of the financial performance of similar companies.According to Cashmere, a bank's financial performance is a measure of the success of the bank's directors, so if the bank is bad, it is impossible for the directors to be replaced.The assessment of the company's performance according to management is as follows: To find out the liquidity factor, namely the company's ability to obtain its financial obligations that must be fulfilled immediately or the company's ability to fulfill its finances when billed. To determine the solvency level, namely the company's ability to fulfill its financial obligations if the company isliquidated both short term and long term financial liabilities.To determine the level of profitability and profitability, indicating the company's ability to generate profits for a certain period. To determine the level of business stability, namely the company's ability to conduct business stably, which is measured by considering the company's ability to pay